2000
DOI: 10.1182/blood.v96.5.1703.h8001703_1703_1708
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the patient population on the risk for heparin-induced thrombocytopenia

Abstract: The frequency of immune heparin-induced thrombocytopenia (HIT) varies among prospective studies. It is unknown whether this is caused by differences in the heparin preparations, the patient populations, or the types of serologic assay used to confirm the diagnosis. Seven hundred forty-four patients were studied from 3 different clinical treatment settings, as follows: unfractionated heparin (UFH) during or after cardiac surgery (n = 100), UFH after orthopedic surgery (n = 205), and low-molecular-weight heparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
292
1
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(311 citation statements)
references
References 23 publications
13
292
1
5
Order By: Relevance
“…Although all patients had received intravenous heparin, the duration of exposure to heparin was variable among them Our multivariate analysis suggested that the duration of exposure to heparin and the thromboembolic complications tended to be associated with the level of optical density in the immunoassay. Regarding the primary disease and the clinical background of these patients, the incidence of HIT was higher among those receiving cardio‐vascular surgery compared to the internal medicine patients, which is compatible with the previous reports . The rate of anti‐PF4/heparin antibody formation, as detected by the immunoassays, was found to be not higher than the reported data.…”
Section: Clinical Characteristics Of Patients Suspected Of Hit In Oursupporting
confidence: 89%
See 1 more Smart Citation
“…Although all patients had received intravenous heparin, the duration of exposure to heparin was variable among them Our multivariate analysis suggested that the duration of exposure to heparin and the thromboembolic complications tended to be associated with the level of optical density in the immunoassay. Regarding the primary disease and the clinical background of these patients, the incidence of HIT was higher among those receiving cardio‐vascular surgery compared to the internal medicine patients, which is compatible with the previous reports . The rate of anti‐PF4/heparin antibody formation, as detected by the immunoassays, was found to be not higher than the reported data.…”
Section: Clinical Characteristics Of Patients Suspected Of Hit In Oursupporting
confidence: 89%
“…Various risk factors of HIT in heparin‐treated adults are reported , and it is known that the different types of heparin as well as the patient‐related factors may affect the development of HIT. In our cases of non‐hemodialysis Japanese patients with suspected HIT, the median age was 66 years (mean 57, range 0–97), and the male/female ratio was almost 1:1 (53 males; 54 female).…”
Section: Clinical Characteristics Of Patients Suspected Of Hit In Ourmentioning
confidence: 99%
“…The frequency of HIT has also been shown to vary among different patient populations (15). Warkentin et al (15) studied 744 patients from three different clinical settings: unfractionated porcine heparin during or after cardiac surgery; unfractionated porcine heparin following orthopedic surgery; and low molecular weight heparin after orthopedic surgery (Table 1). In patients administered unfractionated heparin the frequency of HIT was 4.9% in the orthopedic patients and 1% in the cardiac patients.…”
Section: Epidemiologymentioning
confidence: 99%
“…If one combines all six studies, a total of 21 patients were found to have a positive test for the HIT antibody (2.6%). This is a low rate of HIT antibody positivity compared to patients after cardiac or orthopedic surgery (Table 1) (15). Very few of the dialysis patients were noted to be thrombocytopenic ( n = 6) and none had severe thrombotic complications.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation